The impact of sovereign wealth funds on international financial stability - Tamara Gomes (Bank of Canada, 2008)
Over the recent period, many emerging-market economies and commodity-exporting nations have experienced unprecedented growth and accumulated substantial amounts of foreign exchange reserves. The management of these foreign reserves has led to the emergence of important financial actors: sovereign wealth funds (SWFs). While SWFs have existed in one form or another since the 1950s, they have recently risen in prominence and been exposed to public scrutiny and debate. The author outlines their possible impact on international financial stability. She concludes that SWFs are long-term investors that can play a stabilizing role in financial markets by supplying liquidity and reducing market volatility. While characteristics such as a lack of transparency highlight the potential for destabilization by one or more SWFs, there is little evidence that this has occurred during the recent period. Similarly, the rise of financial protectionism, as host countries adopt rules to protect sensitive industries, might unduly restrict global capital flows, but it is not likely to destabilize the international financial system.
Keywords: F21; F31; F32; G15; 330; Financial stability; Recent economic and financial developments; Währungsreserven; Staatsfonds; Gleichgewichtiges Wachstum; Gesamtwirtschaftliche Liquidität; Volatilität; Kapitalmobilität; Welt